ChemInform Abstract: Palladium‐Catalyzed Asymmetric Allylic Alkylation of Cyclic Dienol Carbonates: Efficient Route to Enantioenriched γ‐Butenolides Bearing an All‐Carbon α‐Quaternary Stereogenic Center. Issue 22 (13th May 2013) - Fournier, Jeremy; Lozano, Oscar; Menozzi, Candice; Arseniyadis, Stellios; Cossy, Janine
Abstract Several methods for the enantioselective synthesis and transformation of the title compounds are presented.